2016
DOI: 10.1007/s00709-016-1000-0
|View full text |Cite
|
Sign up to set email alerts
|

Ductular reaction, cytokeratin 7 positivity, and gamma-glutamyl transferase in multistage hepatocarcinogenesis in rats

Abstract: Hepatocellular carcinoma (HCC) is the most common primary malignancy of the liver and is characterized by multistage formation. The presence of ductular reaction, cytokeratin 7 positivity (PCK7), and increased levels of gamma glutamyltransferase (γGT) has been observed during liver carcinogenesis and contribute to tumor progression. Our goal was to evaluate the ductular reaction in multistage carcinogenesis and to correlate PCK7 and γGT levels with tumor incidence, histological characteristics, liver DNA damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…[48] Studies showed an extensive DR in advanced HCC and a strong correlation between cytokeratin 7 expression and the poor prognosis and aggressiveness of HCC. [49] In our data, strong expression of both hepatic CSC markers (CD24 and EpCAM) and hypoxia marker (CA9) was detected in DR cells. We speculated that hypoxia might be involved in proliferative DRs, eventually contributing to the development of an aggressive HCC phenotype.…”
Section: Discussionsupporting
confidence: 57%
“…[48] Studies showed an extensive DR in advanced HCC and a strong correlation between cytokeratin 7 expression and the poor prognosis and aggressiveness of HCC. [49] In our data, strong expression of both hepatic CSC markers (CD24 and EpCAM) and hypoxia marker (CA9) was detected in DR cells. We speculated that hypoxia might be involved in proliferative DRs, eventually contributing to the development of an aggressive HCC phenotype.…”
Section: Discussionsupporting
confidence: 57%
“…FPR fibrinogen to prealbumin ratio, GPR gamma-glutamyl transpeptidase to platelet ratio, AFP-NHCC alpha-fetoprotein-negative hepatocellular carcinoma, AFP alpha-fetoprotein, CH chronic hepatitis, LC liver cirrhosis, BCLC Barcelona Clinic Liver Cancer elevated in metabolic-induced hepatic injury [40], was observed in this study. Salvatore et al [41] demonstrated that the level of serum GGT elevated with the process of liver carcinogenesis and promoted tumor progression in an HCC animal model of male Wistar rats. Serum levels of GGT could also help with the selection of further treatment and clinical outcomes for patients with HCC [42].…”
Section: Discussionmentioning
confidence: 99%
“…37 The current study confirmed the 2) was a significant predictor of poor survival (HR 1.765, P<0.001), which echoed some published results consummately. [37][38][39] Though AFP level is not included as an indicator in the other four current staging or scoring systems, as a classic tumor marker for HCC, it has long been known that AFP can measure the response to hepatectomy and predict individual survival. Further, the inclusion of AFP improved the predictive performance of the current models; the C-indices of the two nomograms were 0.745 for OS and 0.738 for DFS with AFP but only 0.740 for OS and 0.737 for DFS without AFP.…”
Section: Discussionmentioning
confidence: 99%